Application of Central Composite Design for Development of Celecoxib Loaded Lipospheres: Formulation and in-vitro Characterization - Patil, Moreshwar; Sonawane, Diksha; Sonawane, Sandeep; Bhambere, Deepak; Kshirsagar, Sanjay (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: This study was initiated to develop celecoxib lipospheres to provide controlled release. It demonstrates the use of central composite design for optimization of liposphere formulation with less number of experiments. The development of formulation is primarily based on poor water solubility, low bioavailability and side effects associated with prolonged administration of celecoxib. Methods: Lipospheres were developed by melt dispersion technique and the effect of amount of ethyl oleate and phospholipon 80H on % entrapment in-vitro drug release was studied using central composite design. Additionally the lipospheres were evaluated for percentage yield, particle size and zeta potential. Differential scanning calorimetry, x-ray diffractometry and scanning electron microscopy was used to identify the melting state, internal structure and surface morphology. Results: Entrapment efficiency of 73.63% was obtained while about 82.51% drug was released. The average particle size was 35μm with homogenously dispersed particles. Celecoxib was found to be completely miscible in lipids with disappearance of crystallinity. The lipospheres were spherical in shape with smooth outer surface. Conclusion: Prolonged release celecoxib lipospheres were developed using central composite design.
Keywords: Celecoxib; Phospholipon 80H; Lipospheres; Central composite design; Melt; dispersion